Packaging and storage studies of coco-granola bar - Quinzon, Primrose Molleno
This study was designed to determine the most suitable packaging material for and to estimate the shelf life of coco-granola bar. Preliminary evaluation of the composition of coco-granola and the physical properties of six packaging films was done. Coco-granola proved high in fat but low in water content making the product susceptible to oxidation and mold growth. The laminated films polyethelene terephthalate/ aluminum/polyethylene ans oriented polypropylene/aluminum/polyethylene showed the least permeability to moisture, oxygen, grease, flavor and odor transmission, thus were used. The sorption isotherm of coco-granola, which was determined by the use of PEC, assumed a slightly sigmoidal curve, typical of most foods. The monolayer value of coco-granola is at Aw of 0.25 and moisture content of 3.30%. The critical moisture was determined by monitoring the microbial load, PV, FFA and sensory attributes of stored coco-granola bars. The critical moisture content was found to be 7.82%. The shelf life of coco granola bar was estimated using the Half Value Period method. Results showed that PET/Al/PE can keep the coco granola bar for 2171 days while OPP/Al/Pe only 1752 days.